Identified risks in project team selection - Харитонов, Юрій Миколайович; Елгина, Елена Владимировна (Eastern-European Journal of Enterprise Technologies, 2013)
Under the current conditions one of the urgent problems in heat-and-power engineering sector in Ukraine is the problem of effective implementing the project reconstruction of local heat supply systems, which relates to a great number of risks determining the possibility of this implementation and the indexes of effectiveness of the corresponding projects and programs. The analysis performed has proved that the comprehensive research which is related to the risk management while selecting the project reconstruction of municipal heat supply systems has not been done. Yet in the article, the solution of the problem of risks identification associated with choosing a project team for the project reconstruction of heat supply systems is presented. The solution of the problem is based on the generalized practical results of the project management reconstruction of municipal heat supply systems and the model of forming the project teams on the basis of “artifact” platforms. On the basis of identified risks it is possible to complete the model of choosing the project team with the dependencies providing the assessment of the potential losses and to make pre-selection of the project team for the project reconstruction of heat supply systems